The relationship between male moth density and female mating success in invading populations of Lymantria dispar. Issue 1 (23rd July 2012) - Tobin, Patrick C.; Onufrieva, Ksenia S.; Thorpe, Kevin W.
Abstract The successful establishment of non‐native species in new areas can be affected by many factors including the initial size of the founder population. Populations comprised of fewer individuals tend to be subject to stochastic forces and Allee effects (positive‐density dependence), which can challenge the ability of small founder populations to establish in a new area. Although the conceptual relationship between initial colony size and establishment success has been previously documented, it is not trivial to estimate precisely the colony size needed to ensure colony persistence. Over the last 40 years, there have been many studies on the probability of mating success of female Lymantria dispar (L.) (Lepidoptera: Lymantriidae) in the USA related to background male moth densities. We were motivated by this wealth of data and sought to combine the results from these prior studies with the goal of estimating a robust measure of the male moth density required to achieve varying levels of female mating success. Although the data are specific to L. dispar, the pheromone communication system in L. dispar is not unique and thus the results of this analysis could be broadly applicable to our general understanding of Lepidoptera mating behavior.